Sarah E. Duffy & Michele I. Feist. Time, Metaphor, and Language. A Cognitive Science Perspective. Cambridge: Cambridge University Press, 2023, pp. 190 - Šeškauskienė, Inesa (Kalbotyra, 2024)
Sarah E. Duffy & Michele I. Feist. Time, Metaphor, and Language. A Cognitive Science Perspective. Cambridge: Cambridge University Press, 2023, pp. 190, ISBN 978-1-107-19403-8, DOI: https//doi.org/10.1017/9781108150101